Synthesis and characterization of forward osmosis membrane for drinking water application - Nadira Atiliya, Abdul Rahim (2014)
As the new technology of water treatment, forward osmosis (FO) has been recognized as one of the developing membrane technologies based on separation process. Generally, forward osmosis is the transport of water across a selectively permeable membrane from a region of higher water chemical potential (feed solution) to a region of lower water chemical potential (draw solution). In order to treat water that can be suitable for drinking water application, a forward osmosis membrane was produced by studying the effect of internal concentration polarization (ICP) as the efficiency of FO membrane processes is significantly limited by it. The thin film composite membranes were synthesized through interfacial polymerization of m-phenylenediamine (MPD) series and trimesoyl chloride (TMC) series at different concentration of MPD & TMC on both series of FO membrane. The thin film composite membrane was characterized in term of water flux, permeability and also solute rejection. The longer reaction time of MPD and TMC solution during interfacial polymerization had increased the layer thickness on the surface of the FO membrane which resulting the performance of the membrane